The Effects of Environmental, Social, and Governance (ESG) and Financial Literacy on Investment Decisions in Capital Market Products in East Java : (Study on College Students as Stock Investors in East Java) - Nabila, Fairuz; Mariana; Haron, Nur Quratun Aini (International Environmental Conferrence on Biosustainability Advancement, 2024)
The purpose of this study is to examine the effects of Environmental, Social, and Governance (ESG) and financial literacy on investment decisions in capital market products in East Java. This research uses quantitative methods. The sampling technique used is probability sampling. Specifically, this study used a cluster random sampling method. The population in this study are college students at universities in East Java. Based on cluster random sampling in sample selection, this research is obtained by 214 respondents. Primary data collection is done by distributing online questionnaires (google forms). The data analysis technique used in this study is descriptive statistical analysis, validity and reliability test, classical assumption test, multiple linear regression test, t test, f test and coefficient of determination with support of SPSS Version 25 software program. The results of this study indicate that both Environmental, Social, and Governance (ESG) and financial literacy have positive and significant effects on investment decisions in capital market products in East Java.